2004
DOI: 10.1079/bjn20041249
|View full text |Cite
|
Sign up to set email alerts
|

The absorption of vitamin E is influenced by the amount of fat in a meal and the food matrix

Abstract: Vitamin E absorption requires the presence of fat; however, limited information exists on the influence of fat quantity on optimal absorption. In the present study we compared the absorption of stable-isotope-labelled vitamin E following meals of varying fat content and source. In a randomised four-way cross-over study, eight healthy individuals consumed a capsule containing 150 mg 2 H-labelled RRRa-tocopheryl acetate with a test meal of toast with butter (17·5 g fat), cereal with full-fat milk (17·5 g fat), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
5
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 17 publications
1
76
5
1
Order By: Relevance
“…The most commonly used current method to measure relative availability is to estimate the area under the plasma vitamin K 1 response curve to the vitamin given in standard and test forms. It is possible that the low levels of absorption found in the present experiments are a consequence of the form in which the dose was given either through the absence of a test meal or incomplete release of vitamin K 1 from the capsule, although previous studies investigating vitamin K 1 and E have used similar capsules and have not reported lower than expected absorption (Suttie et al, 1988;Jeanes et al, 2004). The earlier estimate of up to 80% absorption was obtained when the standard vitamin K 1 dose was provided in milk with a meal of bread and cheese (Shearer et al, 1970;Shearer et al, 1974).…”
Section: Discussionmentioning
confidence: 75%
“…The most commonly used current method to measure relative availability is to estimate the area under the plasma vitamin K 1 response curve to the vitamin given in standard and test forms. It is possible that the low levels of absorption found in the present experiments are a consequence of the form in which the dose was given either through the absence of a test meal or incomplete release of vitamin K 1 from the capsule, although previous studies investigating vitamin K 1 and E have used similar capsules and have not reported lower than expected absorption (Suttie et al, 1988;Jeanes et al, 2004). The earlier estimate of up to 80% absorption was obtained when the standard vitamin K 1 dose was provided in milk with a meal of bread and cheese (Shearer et al, 1970;Shearer et al, 1974).…”
Section: Discussionmentioning
confidence: 75%
“…Because vitamin E is a fat-soluble nutrient, it is widely accepted that dietary lipid is required for the absorption of vitamin E (8,9). Research that used an in vitro digestion model showed that a-tocopherol bioavailability was promoted by increasing the amount of soybean oil added to salad purée, because the micellarization of a-tocopherol during digestion was enhanced (10).…”
Section: Introductionmentioning
confidence: 99%
“…5 g fat (P <0 . 001) (69) . It has been shown that during the absorptive phase there is no discrimination between vitamin E forms (70) , but a number of biokinetic studies have demonstrated the preferential secretion of a-tocopherol in VLDL over other vitamin E forms (70) , so that there is a retention of a-tocopherol in the body (71) .…”
Section: Targeted Approachesmentioning
confidence: 99%